How to construct a Time Machine. - Jarry, Alfred; Bal, Mieke; Osborne, Peter (Milton Keynes : MK Gallery, 2015)
Cage, John ; Callanan, Martin John ; Campbell, Jim ; Cleijne, Edgar & Gallagher, Ellen ; Collishaw, Mat ; Ewan, Ruth ; Hsieh, Tehching ; Kawara, On ; Lumière, Louis ; Marker, Chris ; Martin, Kris ; Méliès, Georges ; Mohr, Manfred ; Moti, Melvin ; Nam June Paik ; Paterson, Katie ; Price, Elizabeth ; Sun Ra ; Raqs Media Collective ; Shin, Meekyoung ; Smrekar, Maja ; The Otolith Group ; Thomson & Craighead ; Wallinger, Mark ; Yass, Catherine
Tentoonstelling 'How to construct a Time Machine, MK Gallery, Milton Keynes, 23.01.2015 - 22.03.2015.
boek
Keywords: Smith, Marquard